To find the quadratic equation with roots \( 3+i \) and \( 3-i \), we can use the fact that the quadratic can be expressed in the form:
\[ x^2 - (r_1 + r_2)x + (r_1 \cdot r_2) = 0 \]
where \( r_1 \) and \( r_2 \) are the roots.
- Calculate the sum of the roots \( r_1 + r_2 \):
\[ (3+i) + (3-i) = 3 + i + 3 - i = 6 \]
- Calculate the product of the roots \( r_1 \cdot r_2 \):
\[ (3+i)(3-i) = 3^2 - i^2 = 9 - (-1) = 9 + 1 = 10 \]
- Substituting these values into the quadratic equation:
\[ x^2 - (r_1 + r_2)x + (r_1 \cdot r_2) = x^2 - 6x + 10 = 0 \]
Thus, the quadratic equation is:
\[ x^2 - 6x + 10 = 0 \]
So, the correct response is:
x² - 6x + 10 = 0